2023
DOI: 10.1680/jstbu.21.00160
|View full text |Cite
|
Sign up to set email alerts
|

Embodied carbon, embodied energy and renewable energy: a review of environmental product declarations

Abstract: Environmental Product Declarations (EPD) to EN 15804 provide information about embodied carbon of construction products – their life cycle greenhouse gas emissions - alongside reporting use of renewable and non-renewable primary energy and secondary fuels amongst other environmental indicators. As the number of EPD to EN 15804 increase, they become a useful data resource to consider these impacts. As we move to reduce the embodied carbon of products, we also need to use renewable energy resources efficiently t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Considering the carbon impacts from the non-renewable energy involved in the A1, A2, and A3 stages, especially for EPD 2 and EPD 3 from Italy, high carbon emissions are expected to correspond to high non-renewable energy use. Anderson and Moncaster 43 revealed that, depending on the renewable energy used in the grid, the energy demand might differ due to transmission losses and lower thermal efficiency therefore, the energy demand might vary based on different electricity grid systems. Therefore, even though the PER was higher in EPD 2 and 3 from Italy than in other EPDs, their GWP results were one of the highest, which might be related to the non-renewables involved during the material production, which may have higher primary energy demand due to transmission losses hence higher embodied impact.
Figure 9.GWP, PER, and PENR comparison of the reviewed EPDs.
…”
Section: Resultsmentioning
confidence: 99%
“…Considering the carbon impacts from the non-renewable energy involved in the A1, A2, and A3 stages, especially for EPD 2 and EPD 3 from Italy, high carbon emissions are expected to correspond to high non-renewable energy use. Anderson and Moncaster 43 revealed that, depending on the renewable energy used in the grid, the energy demand might differ due to transmission losses and lower thermal efficiency therefore, the energy demand might vary based on different electricity grid systems. Therefore, even though the PER was higher in EPD 2 and 3 from Italy than in other EPDs, their GWP results were one of the highest, which might be related to the non-renewables involved during the material production, which may have higher primary energy demand due to transmission losses hence higher embodied impact.
Figure 9.GWP, PER, and PENR comparison of the reviewed EPDs.
…”
Section: Resultsmentioning
confidence: 99%
“…The importance of inclusion in policy was evident in the consideration of heritage, and heritage is now a driver for retention on some masterplan sites even without this regulation (Baker et al 2021). Decisions on the case study sites were made over a decade ago, and subsequent developments in understanding mean that there is now a growing recognition of the importance and extent of embodied carbon (Anderson & Moncaster 2022). If the inclusion of embodied as well as operational environmental impacts gains more weight within policy, particularly at the national level, it would seem highly likely to become a key driver towards the retention of buildings.…”
Section: Discussionmentioning
confidence: 99%
“…In 2023, extensive works have been reported in a LCA based doctoral work 12 exploring the role of EPD's in reducing embodied carbon to facilitate sustainable design and construction. This research offers an update on the availability of embodied carbon data and discusses the multi-organizational moves in the UK on assembling more EPD-led material information.…”
Section: Review Of Databases and Assessment Toolsmentioning
confidence: 99%
“…This database aims to provide access to a large number of EPD's. The author 12 points out that there is insufficient know-how of scope and availability of EPD's in the UK.…”
Section: Review Of Databases and Assessment Toolsmentioning
confidence: 99%